An experimental study on the wall collision of micro-sized graphite particles by high-speed photomicrography. (July 2020) - Zhang, Yiyang; Fang, Zhu; Zhao, Shumiao; Wei, Mingzhe; Wu, Xinxin; Sun, Libin
Abstract: The micro-sized graphite dust plays an important role in pebble-bed high temperature gas-cooled reactors, for the close relation with the fission products (FPs). However, an accurate estimation of the deposition rate of graphite dust is still challenging, due to the irregular shape of the particles. Particularly, a key parameter, the critical sticking velocity, remains unclear. Few experimental or theoretical investigations have been reported on the wall collision of graphite particles. As a result, the particle-wall model for the graphite particles in multiphase CFD is often quite crude, which is either models for spherical particles or even hit-and-stick assumptions. To address this issue, we present an experimental study on the wall collision of natural micro-sized graphite particles. The high-speed photography together with a microscope is used to dynamically film the wall collision process of micro-sized graphite particles. Various phenomena such as sticking, rebound and fragmentation are observed. The images show that the irregular lamellar graphite particles prefer the side-to-face orientation rather than the face-to-face orientation. Although the incident angle is usually small, the rebound angles are scattered and nicely follow a Gaussian distribution due to the irregular shape. With the increase of the particle size, the critical sticking velocity decreases, and correlated with the particle size in a power-law relation. As the incident velocity increases, the restitution coefficient increases first and then decreases, which becomes stable and follows the Gaussian distribution at high impact velocities. By incorporating the size effect, surface adhesion and local dissipation, we further present a semi-empirical correlation for the restitution coefficient over a wide range of particle size and incident velocity. Our work can provide some insights into the nature of sticking phenomena of graphite particles in HTGR. Highlights: The wall collision of irregular lamellar graphite particles down to 3 μm is filmed. Critical sticking velocity is correlated with particle size in power-law relation. A correlation for COR is established over wide range of collision conditions. The rebound angle is scattered and nicely follows a Gaussian distribution.